Implementing Pair-Work Activities Using Functional Language Examples To Improve The Students’ Speaking Skill Of Smp Negeri 21 Samarinda - Esti Royani (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2016)
This research aims to find out the solutions of the students' problem on speaking skill , through implementing pair work activities using functional languages examples.The goal of teaching speaking skill is to communicate efficiency. Learners should be able to make themselves understood, using their current proficiency to the fullest. They should try to avoid confusion in the message due to faulty pronunciation, grammar, or vocabulary, and to observe the social and cultural rules that apply in each communication situation.Learning to speak English requires more than knowing its grammatical and semantic rules. Students need to know how native speakers use the language in the context of structured interpersonal exchange. Effective oral communication requires the ability to use the language appropriately in social interactions. This research used a classroom action research ( CAR )  of the targeted to the first year students of SMP Negeri 21 Samarinda to be achieved. Based on analysis and discussion of the findings that the implementation of pair – work activities using functional language examples in teaching speaking was useful  to improve the students' speaking competence. Both pair – work and functional examples provided good models and facilitated students to practice and to keep repeating using the spoken language to achieve a particular level proficiency.